Фильтрация помехи неоднородной регулярной структуры в тепловом контроле - Лучанинова, А. Ю. (ХНУРЕ, 2019)
In this work the thermal-physical model of the starved spots in the honey-comb sandwich detection process was considered. The interferences caused by an emissivity fluctuation and a glue film inhomogeneity suppression way based on corresponding technique of data processing choice was suggested.